Dorsal periaqueductal gray simultaneously modulates ventral subiculum induced-plasticity in the basolateral amygdala and the nucleus accumbens - Horovitz, Omer; Richter-Levin, Gal (Frontiers in Behavioral Neuroscience, 2015)
The ventral subiculum of the hippocampus projects both to the basolateral amygdala, which is typically, associated with a response to aversive stimuli, as well as to the nucleus accumbens, which is typically associated with a response to appetitive stimuli. Traditionally, studies of the responses to emotional events focus on either negative or positive affect-related processes, however, emotional experiences often affect both. The ability of high-level processing brain regions (e.g. medial prefrontal cortex) to modulate the balance between negative and positive affect-related regions was examined extensively. In contrast, the ability of low-level processing areas (e.g. periaqueductal grey - PAG) to do so, has not been sufficiently studied. To address whether midbrain structures have the ability to modulate limbic regions, we first examined the ventral subiculum stimulation’s (vSub) ability to induce plasticity in the basolateral amygdala (BLA) and nucleus accumbens (NAcc) simultaneously in rats. Further, dorsal PAG (dPAG) priming ability to differentially modulate vSub stimulation induced plasticity in the BLA and the NAcc was subsequently examined. vSub stimulation resulted in plasticity in both the BLA and the NAcc simultaneously. Moreover, depending on stimulus intensity, differential dPAG priming effects on LTP in these two regions were observed. The results demonstrate that negative and positive affect-related processes may be simultaneously modulated. Furthermore, under some conditions lower-level processing areas, such as the dPAG, may differentially modulate plasticity in these regions and thus affect the long-term emotional outcome of the experience.